Inferring species interactions from long-term monitoring programs: Carnivores in a protected area from southern Patagonia - Díaz Ruiz, Francisco (2020)
Protected areas recently created in Argentina often include previously degraded lands, such as sheep ranches in the Patagonian deserts. We show the results of a 14-year monitoring program of three formerly persecuted carnivores, the culpeo fox (Lycalopex culpaeus), the South American grey fox (Lycalopex griseus) and the puma (Puma concolor), in two abandoned sheep ranches that were incorporated into a Patagonian national park approximately 25 years ago. The culpeo fox population underwent an average annual decline of 10-23%, whereas the grey fox and puma populations increased at an average annual rate of 7% and 19%, respectively. The grey fox's increasing trends were strongly correlated with the decline of the culpeo fox, whereas the correlations between the fox and puma trends were weaker. Culpeo fox decline was stronger in the ranch where sheep and predator controls had been removed earlier. These relationships between species trends support the competitive release hypothesis, assuming that puma competition with the culpeo fox for trophic resources is stronger than competition with the grey fox, and that the puma can exclude culpeo foxes through interference. Species trends suggest a competitive hierarchy between fox species, with grey fox being the inferior competitor. However, mechanisms other than competition could not be discounted. Our study illustrates how long-term monitoring of interacting species allows a better understanding of ecological processes and wildlife ecology.